2022
DOI: 10.1021/acs.iecr.1c04265
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Tensile Strength and Density Prediction Models for Semi-Interpenetrating Polymer Network from Fluoroelastomer and Poly(dimethylsiloxane)

Abstract: Interpenetrating polymer networks (IPNs) have attracted considerable attention due to the forced miscibility compared with usually incompatible blends. In this article, semi-IPNs composed of linear fluoroelastomer F2314 and cross-linked poly­(dimethylsiloxane) (PDMS) were synthesized by changing the mass ratio of F2314/PDMS and the molar ratio of [NCO]/[OH], and the properties of the prepared samples were studied. Differential scanning calorimetry (DSC) and atomic force microscopy (AFM) confirmed the F2314/PDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…One common fabrication method for IPNs is to polymerize two monomers simultaneously, and at least one of the two monomers forms a network. ,, If the resulting polymers are thermodynamically incompatible, the initially homogeneous reaction mixture becomes phase-separated as a result of polymerization. However, the microstructure is kinetically trapped in a nonequilibrium state as cross-linking occurs, resulting in incomplete phase separation and mixing between the normally incompatible polymers at the nanoscale. , This incomplete phase separation is traditionally observed by ensemble-based measurements of macroscopic samples, such as shifts in glass transition temperature ( T g ) and changes in X-ray scattering intensity. ,, In a previous study, we used small-angle X-ray scattering (SAXS) to measure the degree of mixing in poly­(dimethylsiloxane)/poly­(methyl methacrylate) (PDMS/PMMA) IPNs by investigating the differences in the scattering length density of the two phases. We showed that the degree of mixing increases as the minority phase fraction decreases .…”
Section: Introductionmentioning
confidence: 99%
“…One common fabrication method for IPNs is to polymerize two monomers simultaneously, and at least one of the two monomers forms a network. ,, If the resulting polymers are thermodynamically incompatible, the initially homogeneous reaction mixture becomes phase-separated as a result of polymerization. However, the microstructure is kinetically trapped in a nonequilibrium state as cross-linking occurs, resulting in incomplete phase separation and mixing between the normally incompatible polymers at the nanoscale. , This incomplete phase separation is traditionally observed by ensemble-based measurements of macroscopic samples, such as shifts in glass transition temperature ( T g ) and changes in X-ray scattering intensity. ,, In a previous study, we used small-angle X-ray scattering (SAXS) to measure the degree of mixing in poly­(dimethylsiloxane)/poly­(methyl methacrylate) (PDMS/PMMA) IPNs by investigating the differences in the scattering length density of the two phases. We showed that the degree of mixing increases as the minority phase fraction decreases .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies illustrated the correlation of hard component content with brittleness in an sIPN system. 35,36 Similarly, the highly cross-linked scaffold network functioned as the hard component in the photocured SIR system and caused lower strain at break above 9.1 wt %. Additionally, increasing scaffold content restricted the mobility of embedded SIR latex particles in the printed green body, compromising the interparticle coalescence during postprocessing.…”
Section: Resultsmentioning
confidence: 99%